1. RESULT OF ENDOSCOPIC SURGERY FOR MIDDLE EAR CONGENITAL CHOLESTEATOMA IN CHILDREN AT NGHE AN OBSTETICS AND PEDIATRIC HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objectives: Evaluate the results of endoscopic surgery for congenital middle ear cholesteatoma at Nghe An Obstetrics and Children's Hospital.Research objects and methods: Cross-sectional descriptive study of 28 children diagnosed with congenital middle ear cholesteatoma and underwent endoscopic surgery to remove cholesteatoma at Nghe An Obstetrics and Children's Hospital from January 1, 2022 to July 30, 2023.Results: After surgery 1 day, 7 days and 14 days, no patient had any symptoms of vomiting or facial paralysis. On the first day after surgery, 67.85% of children showed signs of pain, crying, and had to use painkillers. By the 7th day, only 3 patients (10.71%) had mild pain, did not use painkillers, and after 14 days, no patients had ear pain. There were 2 patients (7.15%) with ear discharge on day 14. Results after 3 months, the rate of intact, bright, shiny eardrum was 82.14%; The rate of perforated eardrum is 7.14%; 1 patient (3.57%) relapsed.Conclusion: Early detection of congenital cholesteatoma through ENT endoscopy is necessary and meaningful in treatment, avoiding complications and recurrence after surgery.
Keywords: Congenital middle ear cholesteatoma, endoscopic surgery